2012
DOI: 10.1063/1.3695093
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anomalous Doppler resonance effects with molybdenum and graphite limiters on HT-7

Abstract: The material of limiter in HT-7 tokamak was changed from graphite to molybdenum in the last experimental campaign. The pitch angle scattering of runaway electrons due to anomalous Doppler resonance effects was observed. The experimental results agree very well with the stable boundary condition expected from the linear resistive theory but only agree with that from the nonlinear evolutionary of runaway-electron distribution theory in low electric field region. The current carried by runaway electrons is the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Several previous studies of the pedestal collapse have reported the abrupt increase of the mm-wave emission intensity, whose frequencies correspond to the ECE harmonics at the edge region [42][43][44][45][46][47]. The details of the generation mechanism in the mm-wave bursts are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies of the pedestal collapse have reported the abrupt increase of the mm-wave emission intensity, whose frequencies correspond to the ECE harmonics at the edge region [42][43][44][45][46][47]. The details of the generation mechanism in the mm-wave bursts are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In this Letter we show for the first time that BMEs in MAST can be attributed to the presence of suprathermal, magnetic-field-aligned electron populations that drive waves in the EC range via the anomalous Doppler instability (ADI). This instability has been observed recently on the HT-7 tokamak [15] and is also believed to play a role in the dynamics of energetic electrons in solar flares [16,17] and the excitation of whistlers in the solar wind [18]. The production and evolution of energetic electron popu lations continue to be of topical interest in the solar context [19].…”
mentioning
confidence: 82%
“…It has been found in over four decades of experiments in low density tokamak plasmas [4][5][6][7][8]11,14 with both Ohmic and lower hybrid current drive, and remains topical. For example, the ADI is believed to explain the recently observed relaxation oscillations in directional hard X-ray signals emitted by the energetic electron population in the HT-7 tokamak 14,15 . These observations reflect the underlying physics of the ADI, which involves a shift of energy from parallel to perpendicular particle motion, accompanied by the excitation of waves at frequency and wavenumber (ω, k) satisfying the anomalous Doppler resonance condition 11 ,…”
Section: The Anomalous Doppler Instability (Adi)mentioning
confidence: 99%